Subtly offending feedback. Issue 4 (7th October 2014) - Krings, Rabea; Jacobshagen, Nicola; Elfering, Achim; Semmer, Norbert K.
Abstract Providing acceptable negative feedback is difficult because it may threaten the receiver's self‐esteem. Studies have established that destructive feedback elicits stronger negative reactions than constructive feedback. However, these destructive conditions were quite strong, implying a clear threat to the self. Because of the importance of protecting one's self‐concept, negative evaluations might be provoked by more subtle cues. Such cues should also be detected by observers. We developed three variants of subtly offending feedback in which mistakes appeared disproportionately serious. In an experimental pilot study, 132 student observers judged the fairness of feedback given to another student. The subtly offending conditions were evaluated as less fair than constructive feedback but as more fair than destructive feedback.